From digital blueprint to chemical reality: methanol to formaldehyde at ambient conditions - Mehta, Shweta; Kasabe, Mirabai; Umbarkar, Shubhangi B.; Joshi, Kavita (Applied Surface Science, 2024)
Partial oxidation of methanol to value added product presents an intriguing yet challenging process. Among these products, formaldehyde is the simplest and one of the most vital aliphatic aldehydes, which has extensive application across various domains. Industrially, silver and iron-molybdenum oxides are used as catalysts for the conversion of methanol to formaldehyde at elevated temperatures (600 degrees C and 250-400 degrees C, respectively). However, in this computational and experimental study, we have demonstrated the efficacy of ZnO as a catalyst. Notably, in the presence of ZnO, methanol readily converts to formaldehyde even under ambient conditions. We employed periodic density functional theory (DFT) to explore (10 1 1) facet of ZnO to elucidate its interaction with methanol. Our comprehensive analysis identified the most active facet (10 1 1) involved in the spontaneous conversion of methanol to formaldehyde. Subsequently, experimental validation supported our theoretical findings, demonstrating the conversion of methanol to formaldehyde with 100% selectivity at room temperature and atmospheric pressure in the presence of ZnO. This study exemplifies the pivotal role of theory in catalyst design.
Keywords: DFT; Formaldehyde; MeOH; ZnO